Unilateral progressive vision loss in tuberculous meningoencephalitis - Kamal, Ronik; Abdullah, Muhammad; Finanda, Clarisa; Firmansjah, Muhammad; Primitasari, Yulia (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
Tuberculosis (TB) is an infectious disease that significantly contributes to global mortality and morbidity. Extrapulmonary TB, such as TB meningitis, often involves ocular manifestations and presents diagnostic challenges, leading to treatment delays and increased mortality rates. A 17-year-old girl presented with progressive, painless vision loss in her right eye over 1 month. Her mother was undergoing TB treatment, and the patient’s body mass index indicated malnutrition. Ophthalmological examination of the right eye revealed a visual acuity (VA) of 2/60, diminished light reaction, 0/38 on the Ishihara test, optic disc pallor, and multiple choroidal white lesions. Examination of the left eye showed a VA of 6/6, diminished light reaction, segmental disc pallor, and a blurred optic disc margin. Cerebrospinal fluid analysis and contrast-enhanced head magnetic resonance imaging were indicative of TB meningitis, and a chest X-ray confirmed pulmonary TB. Optical coherence tomography revealed thinning of both eyes’ retinal nerve fiber layers. The patient was treated with anti-TB therapy and corticosteroids. This case underscores that delayed diagnosis of ocular TB can lead to significant vision impairment. Comprehensive diagnostic investigations, including neuroimaging, are imperative for managing complex cases, especially in TB-endemic regions, ultimately improving patient outcomes.